Usmíření jako konečné stadium řešení konfliktu - Oberpfalzerová, Hana (Lidé města, 2024)
The aim of this synoptic article is to provide the reader with a basic understanding of the issue of reconciliation after open armed conflict. We shall mention the most significant concepts, theories amd authors in this field; however, the article does not and cannot cover all concepts in great detail due to restricted space. The article is divided into three parts, which consecutively answer the following three questions: what is the role of reconciliation in the process of conflict resolution and in the prevention of further conflicts? What are the definitions of reconciliation, and what are its various concepts and dimensions? What are the mechanisms that lead to reconciliation, and what are the obstacles that this process faces? The discussed literature concentrates on the role of reconciliation in violent, protracted and intractable conflicts. The article itself falls under the category of peace and conflict studies, in the field of conclict resolution and of the so-called peace psychology.